Analisis Prevalensi dan Faktor-Faktor yang Mempengaruhi Swamedikasi Sebelum dan Selama Pandemi COVID-19: Studi pada Mahasiswa Kesehatan di Jawa Tengah - Indriyati Hadi Sulistyaningrum; Arifin Santoso; Fildza Huwaina Fathnin; Dian Mila Fatmawati (Universitas Muhammadiyah Surakarta, 2022)
Self-medication is defined as an attempt to treat using medicines purchased at pharmacies or drug stores without a doctor's prescription. There is currently a public health emergency due to the emergence of COVID-19. This study aimed to assess the prevalence of self-medication before and during the COVID-19 pandemic among health students in Central Java and its associated factors. This cross-sectional survey involved 384 respondents with teknik snowball sampling using an online questionnaire that had been tested for validity and reliability. The data were analyzed with descriptive and inferential statistics, namely bivariate analysis and multivariate analysis. Bivariate analysis with Chi square and Wilcoxon to compare sociodemographic characteristics with self-medicating before and during the pandemic. Furthermore, multivariate analysis was carried out using logistic regression to see the factors that most influenced individual desires to self-medicate (p0.05). Based on the analysis, the results showed that the prevalence of self-medicating among health students in Central Java has increased from before the pandemic (58.6%) to (78.6%) during the pandemic. Self-medication was mostly done by women (84.4%), aged 18-40 years (99.2%). Places to buy drugs at pharmacies (91%) and considerations in choosing drugs by looking at drug brands (52%). Another factor of respondents doing self-medication is due to previous experience using similar drugs (49%), the factor of information sources from the internet (46%). The results of the study concluded that there were differences between age, gender, level of education, understanding of self-medication, experiencing pain in the last 3 months, physical activity and suggestions from others affecting individual desires for self-medication before and during the COVID-19 pandemic. Furthermore, it is necessary to conduct education and monitoring related to self-medication carried out by students so that the treatment carried out is appropriate and rational.